2014
DOI: 10.5350/semb2014480106
|View full text |Cite
|
Sign up to set email alerts
|

Lomber diskopati tanılı olgulara uyguladığımız epidural kortikosteroid enjeksiyonunun klinik sonuçları

Abstract: Lomber diskopati tanılı olgulara uyguladığımız epidural kortikosteroid enjeksiyonunun klinik sonuçları Amaç: Lomber epidural steroid enjeksiyonları (LESE) lomber disk hernisinde (LDH) kullanılan minimal invaziv tedavi yöntemleridir. Bu çalışmada, konservatif tedavi yöntemleri ya da cerrahi tedaviyle iyileşmeyen bel ağrısı şikayeti olan hastalara uyguladığımız LESE tedavisinin, semptomlar ve yaşam kalitesine etkisini incelemeyi amaçladık. Gereç ve Yöntem: Çalışma, kliniğimize konservatif tedaviye dirençli lombe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[15,30] Oncu et al investigated in 2014 the effects of lumbar epidural steroid injection in patients with radiculopathy and they reported that lumbar epidural corticosteroid injections were effective in patients with radiculopathy during the first three months after treatment. [31] We comprehended that the complaints of four patients whose VAS results were not changed in the second-week evaluation after the procedure was longer than six months (chronic) in the present study. We found that this result was consistent with the studies in the literature.…”
Section: Discussionmentioning
confidence: 48%
“…[15,30] Oncu et al investigated in 2014 the effects of lumbar epidural steroid injection in patients with radiculopathy and they reported that lumbar epidural corticosteroid injections were effective in patients with radiculopathy during the first three months after treatment. [31] We comprehended that the complaints of four patients whose VAS results were not changed in the second-week evaluation after the procedure was longer than six months (chronic) in the present study. We found that this result was consistent with the studies in the literature.…”
Section: Discussionmentioning
confidence: 48%